Current knowledge on the cave fungi in Brazilian biomes - Prazeres, José Fredson da Silva Alves dos; Bernard, Enrico; Souza-Motta, Cristina Maria de; Bento, Diego de Medeiros; Silva-Júnior, Edson Nilton de Moura; Barbier, Eder [UNESP]; Fonseca, Emily Oliveira; de Lima, Joenny Maria da Silveira; Carvalho, João Lucas Vitório Ribeiro; Miranda, Lorena Souza; Pereira, Olinto Liparini; Barbosa, Renan do Nascimento; et al. (Elsevier, 2025)
Cave fungi represent a diverse array of species that underwent speciation beyond their subterranean confines, providing several benefits to the biosystems they inhabit. Caves are hotspots for diverse fungal species. Despite the large number of known caves in Brazil, a megadiverse country, only a few studies have assessed the mycobiota in the karstic ecosystem. Herein, we present a state-of-the-art bibliometric review of the cave fungi in Brazil discussing the past and ongoing research in the country and highlighting the important historical milestones and aspects of Brazilian speleomycology. Based on the data from 30 publications, only the mycobiota in 30 caves in four Brazilian biomes (Amazon, Atlantic Forest, Cerrado, and Caatinga) have been assessed to date. Moreover, 292 fungal genera belonging to six phyla (Ascomycota, Basidiomycota, Basidiobolomycota, Chytridiomycota, Mucoromycota, and Mortierellomycota) have been recorded, and a few operational taxonomic units have been identified as Rozellomycota and Kickxellomycota. Sordariomycetes is the most representative class identified to date. Aspergillus and Penicillium are the most frequent genera detected in all surveyed caves. Cerrado biome accounts for the largest number of studies (18), both for inventoried caves and fungal communities, and 70% of fungal genera have been exclusively recorded in this biome. Nearly half of the cave fungi known worldwide are found in only 30 caves in Brazil (approximately 0.1% of the known caves in the country), emphasising the importance of Brazilian caves as reservoirs of overall biodiversity. Speleomycology focuses on this “invisible diversity,” highlighting the necessity of cave conservation, even in megadiverse countries such as Brazil.
Keywords: Biospeleology; Brazilian fungal estimate; Cave environment; Fungal diversity; Speleomycology